Decolonizing Historical Consciousness Through Digital Inquiry: Student Experiences with Indigenous Peace: interpretative phenomenological analysis - Sumiatie; Leo Agung Sutimin; Sariyatun (Proceeding International Conference on Digital Education and Social Science, 2025)
Understanding how students experience engagement with marginalized historical narratives remains critical for developing an equitable curriculum in postcolonial education systems. This study explores how ethnically diverse Indonesian high school students experience and make sense of inquiry-based digital learning centered on the 1894 Tumbang Anoi Peace Accord, a reconciliation event systematically excluded from Indigenous Dayak history. Using interpretative phenomenological analysis, eight purposively selected Grade 11 students (four Dayak, four non-Dayak) participated in semi-structured interviews lasting 60 to 90 minutes, conducted four to eight weeks after completing a three-week scaffolded e-module. Interviews were audio-recorded, transcribed verbatim, and analyzed through iterative coding that captured the descriptive, linguistic, and conceptual dimensions of lived experience. Four superordinate themes emerged: Emotional Resonance and Cultural Awakening, Transformation from Marginalization to Cultural Pride, Peace as Embodied Practice, and Indigeneity as National Belonging. Dayak participants described profound shifts from ethnic shame to pride, whereas non-Dayak students developed intercultural solidarity and expanded conceptions of national identity. All participants reported visceral bodily responses and recognized peace as an active practice applicable to contemporary conflicts. Findings demonstrate that centering previously excluded Indigenous histories through scaffolded digital inquiry generates profound affective and identity transformations that are invisible to traditional assessment, contributing methodologically by demonstrating the utility of interpretative phenomenological analysis for evaluating digital interventions and practically by providing evidence for equity-oriented curriculum reform.